STRATEGI KOMUNIKASI ADVOKASI KEBIJAKAN LARANGAN PENGGUNAAN KANTONG PLASTIK SEKALI PAKAI DI KABUPATEN MALANG - Asmoro, Bramantyo Tri (Sintesa, 2025)
The advocacy campaign for the ban on the use of single-use plastic bags in Malang Regency aims to reduce the negative impact of plastic waste on the environment and public health. To effectively conduct this advocacy campaign, a well-formulated communication strategy is essential. The formulation of the advocacy communication strategy utilizes the SOSTAC model (Situation Analysis, Objectives, Strategy, Tactics, Action, Control). This research is qualitative, with data sources extracted from reports, scientific publications, and media outlets, and data analysis conducted descriptively. The purpose of this research is to formulate a communication strategy for advocating the policy to ban the use of single-use plastic waste in Malang Regency. The primary goal of this advocacy is to encourage the Malang Regency Government to issue a policy banning the use of single-use plastic bags in the region. The strategy formulated involves various stakeholders, including the government, the community, and business actors, with an engaging and systematic communication approach. The results of the study show that collaboration among all parties is crucial in achieving public awareness and support for the ban on single-use plastics. This success is expected to serve as a model for other regions in Indonesia